The diagnostic value of FNAC in assessment of superficial palpable lymph nodes: a study of 395 cases - Pinki Pandey; Alok Dixit; N.C. Mahajan (Al Ameen Medical College, 2013)
Objective: To validate the importance of FNAC in cases of lymphadenopathies by studying the different cytomorphological patterns associated with various lymphadenopathies. Methods: A study was carried out over a period of five years in a tertiary care teaching hospital. FNAC of 395 patients presenting with superficial palpable lymphadenopathy was reviewed, correlated with final histopathological diagnoses, wherever available, and concordance and discordance rates were evaluated. Result: Of the 395 patients with palpable lymphadenopathy, among 277 cases of benign lesions, reactive hyperplasia 121(30.63%) ranked on top, followed by tuberculous lymphadenitis 113(28.60%) and by pyogenic lymphadenitis 43(10.88%). And among the 113 cases of malignant lesions, 90(22.78%) cases of metastatic carcinoma were followed by malignant lymphomas 23(5.82%) cases; including NHL 15(3.80%) and HL 8(2.02%). AFB was confirmed in 78(69.02%) cases by ZN staining of FNAC smears. The nodal site sampled most frequently was cervical group of lymph nodes. Histopathology was available in 45 cases. The cytological and histological concordance was determined in 40 malignant cases. Conclusion: FNAC is a simple technique, easy to perform, quick and cost effective in diagnosis of lymphadenopathies which also serves as an excellent preliminary screening procedure. It obviates the need for unnecessary surgical excision of nodes.